‘Het zijn onze armen’: An overview of the Cape Synod of the Dutch Reformed Church’s welfare efforts, 1824-2024 - Kotze, Este (Stellenbosch Theological Journal, 2024)
Since its inception in 1824, the Western Cape Synod of the Dutch Reformed Church (DRC) has played a key socio-economic role as provider of a range of poor relief strategies. However, the purpose of these charitable efforts was not solely rooted in theological principles. In the nineteenth and twentieth century South African context, poor relief work carried distinct political undertones, particularly surrounding the so-called ‘poor white problem’. A substantial body of literature has emerged surrounding ‘poor whites’ and the political efforts employed to ‘save’ them in the decades before the implementation of apartheid. While the Church’s poor relief schemes are often mentioned as significant in these studies, the Church’s poor relief systems and their development over time remain understudied. This paper identifies and discusses five distinct phases of development of DRC poor relief strategies over the past two centuries (1824-1860s; c. 1860-1900s; 1910-1940; c. 1940-1980s; and 1990-present) and argues that these stages and the practical implementation of the Church’s poor relief efforts has been notably shaped by the contemporary socio-economic and socio-political zeitgeist in which it was embedded.